Competência de redes para o estabelecimento de acordos de cooperação: uma validação de escala para o contexto brasileiro - Pesce, Ricardo Oliveira (Universidade do Vale do Rio dos Sinos, 2020)
The great challenge companies are presently facing is finding ways to increase cost efficiency and meet demand at a competitive price, as well as the creative capacity to compete in future markets through the diversity of products, new products and adequate service. In this line of thought, Cooperation Networks have become important external sources for companies to achieve their goals. For this, skills and actions are required on the part of network participants, which was defined by Ritter (1999) as Network Competence. The objective of this research is to validate the network competence research instrument developed by Ritter, Wilkinson, and Johnston (2002) in the Brazilian context. This is a cross-sectional study with a descriptive quantitative approach, with a sample that included 99 companies located in the city of Porto Alegre and in the interior of the state of Rio Grande do Sul. Four Cooperation Networks were contacted, including 1 supermarket chain, 2 from the field of furniture and planned environments and 1 with operations in the sale of construction material. The instrument used in this research was a questionnaire divided into 9 blocks, with 45 questions. The research results revealed a new scale in the local sample, with good factorial loads, and similar results to the ones found by Ritter and Gemünden (2003). The validation of this research instrument is of great importance, as it can be used for research on Network Skills in other companies or Cooperation Networks.
Keywords: Redes de cooperação; Competência de redes; Validação de escala; Cooperation networks; Network competence; Scale validation; ACCNPQ::Ciências Sociais Aplicadas::Administração